Assessment of a 2D electronic portal imaging devices-based dosimetry algorithm for pretreatment and in-vivo midplane dose verification - Ali Jomehzadeh; Parvaneh Shokrani; Mohammad Mohammadi; Alireza Amouheidari (Advanced Biomedical Research, 2016)
Background: The use of electronic portal imaging devices (EPIDs) is a method for the dosimetric verification of radiotherapy plans, both pretreatment and in vivo. The aim of this study is to test a 2D EPID-based dosimetry algorithm for dose verification of some plans inside a homogenous and anthropomorphic phantom and in vivo as well. Materials and Methods: Dose distributions were reconstructed from EPID images using a 2D EPID dosimetry algorithm inside a homogenous slab phantom for a simple 10 × 10 cm2 box technique, 3D conformal (prostate, head-and-neck, and lung), and intensity-modulated radiation therapy (IMRT) prostate plans inside an anthropomorphic (Alderson) phantom and in the patients (one fraction in vivo) for 3D conformal plans (prostate, head-and-neck and lung). Results: The planned and EPID dose difference at the isocenter, on an average, was 1.7% for pretreatment verification and less than 3% for all in vivo plans, except for head-and-neck, which was 3.6%. The mean γ values for a seven-field prostate IMRT plan delivered to the Alderson phantom varied from 0.28 to 0.65. For 3D conformal plans applied for the Alderson phantom, all γ1% values were within the tolerance level for all plans and in both anteroposterior and posteroanterior (AP-PA) beams. Conclusion: The 2D EPID-based dosimetry algorithm provides an accurate method to verify the dose of a simple 10 × 10 cm2 field, in two dimensions, inside a homogenous slab phantom and an IMRT prostate plan, as well as in 3D conformal plans (prostate, head-and-neck, and lung plans) applied using an anthropomorphic phantom and in vivo. However, further investigation to improve the 2D EPID dosimetry algorithm for a head-and-neck case, is necessary.